Citizenship Status Influencing Self-Concept Among Teenagers - Aminuddin Ibrahim Lastar; Nor Masitah Ahamad Shaleh; M.Pusenthi P.Maniam; Siti Nur Nadia Ahmad Razil (Asian Social Work Journal, 2017)
The purpose of this case study is to identify the influence of citizenship status in teenagers’ self- concept who are at Kuala Lumpur Krash pad. The study is specifically conducted among those teenagers who do not hold any citizenship status and attending KL Krash pad regulary. This is a qualitative study in which the data was gatherd by conducting a face to face session using a structured interview questions. The content of the interview was divided into five sections namely; demographic, experiences, behavioural, status, and social interactions (communication). There were six participants involed in this study who were from the range of age 13-18 years old. The data was then analised for key words and gategorised under specific themes in which became the factors in contributing the influence of citizenship status on self-concept among the non Malaysian /boaderless teenagers who are attending programs at Kuala Lumpur Krash Pad.